Pengaruh Strategi Digital Marketing dan Harga Jual Terhadap Volume Penjualan Kartu Indosat Ooredoo Hutchison - Dea Fitria Anwar; Leny Muniroh; Ecin Kuraesin (Indonesian Journal of Innovation Multidisipliner Research, 2023)
This research aims to determine the influence of digital marketing strategy and selling price on sales volume simultaneously and partially on sales volume at PT. Sakalaguna Semesta Ciseeng Bogor. This research uses a quantitative approach method where the aim is to present research results in the form of more accurate numbers. The number of samples used in this research was 136 people consisting of active consumers of PT. Sakalaguna Semesta Ciseeng. The results of data analysis using SPSS version 26 are as follows: the regression equation Y= 2.949 + 0.191 X1 + 0.194 X2 is obtained. The correlation coefficient test shows = 0.601, meaning there is a strong relationship between the digital marketing strategy variables and selling price on sales volume. The partial hypothesis test shows t = 7.470 and t table = 1.656, indicating that there is a relationship between digital marketing strategy and sales volume. The partial hypothesis test shows t = 7.676 and t table = 1.656, indicating that there is a relationship between selling price and sales volume. Hypothesis test F calculated 37.538 > 3.06, thus H0 is rejected and H3 is accepted, this shows that there is a significant simultaneous influence between digital marketing strategy and selling price on sales volume at PT. Sakalaguna Semesta Ciseeng Bogor.